Pemberdayaan Masyarakat Melalui Pelatihan Kain Perca Untuk Meningkatkan Perekonomian Rumah Tangga Di Kragan Gedangan Sidoarjo - Febriani, Maya (STAI Miftahul ULa Nganjuk, 2023)
Kragan Village has MSME potential because it is close to the industrial center. Many tailors are scattered around the industrial area, but the patchwork is still discarded and not used by tailors. Departing from this potential, through the Service learning approach, the team assisted in the use of unused patchwork into a suitable product. The results of this assistance show that training on the use of patchwork provides a good opportunity to implement the reuse of wasted patchwork into wearable products. The impact of this activity is able to provide economic added value from the results of processed patchwork products.